Miniaturized microdosimeters for hadron therapy - Selva, Anna; Bianchi, Anna; Fazzi, Alberto; Conte, Valeria (Frontiers in Sensors, 2025)
Microdosimetry measures the stochastic fluctuations of energy imparted by radiation at the micrometer level and can provide measurable quantities linked to biological effectiveness. Reference instruments are Tissue-Equivalent Proportional Counters, gas-filled detectors operated in single-event proportional mode with a chemical composition similar to biological materials. The Legnaro National Laboratories of INFN have extensive experience in the design and construction of miniaturized microdosimetric gas counters able to sustain the high fluence rates of hadron therapy beams without significant pile-up effects. This work discusses the current state-of-the-art detection technologies in microdosimetry for hadron therapy, with a focus on miniaturized gas counters. It describes in particular the development of engineered compact detectors optimized for use in clinics, featuring enhanced stability and reproducibility of response, carried out within INFN projects.